A new species of Hirudo (Annelida: Hirudinidae): historical biogeography of Eurasian medicinal leeches. Issue 1 (December 2016) - Saglam, Naim; Saunders, Ralph; Lang, Shirley; Shain, Daniel
Abstract Background Species ofHirudo are used extensively for medicinal purposes, but are currently listed as endangered due to population declines from economic utilization and environmental pollution. In total, five species ofHirudo are currently described throughout Eurasia, with Turkey being one of the major exporters of medicinal leech, primarilyH. verbana . Results To define the distribution ofHirudo spp. within Turkey, we collected 18 individuals from six populations throughout the country. Morphological characters were scored after dorsal and ventral dissections, and Maximum Likelihood (ML) and Bayesian Inference (BI) analyses resolved phylogenetic relationships using mitochondrial cytochromec oxidase subunit I (COI), 12S ribosomal RNA (rRNA), and nuclear 18S rRNA gene fragments. Our results identify a new species of medicinal leech, Hirudo sulukii n. sp, in Kara Lake of Adiyaman, Sülüklü Lake of Gaziantep and Segirkan wetland of Batman in Turkey. Phylogenetic divergence (e.g., 10–14 % at COI), its relatively small size, unique dorsal and ventral pigmentation patterns, and internal anatomy (e.g., small and pointed atrium, medium-sized epididymis, relatively long tubular and arc formed vagina) distinguishH. sulukii n. sp. from previously describedHirudo sp. Conclusions By ML and BI analyses, H. sulukii n. sp. forms a basal evolutionary branch of Eurasian medicinal leeches. Phylogeographic interpretations of the genus identify a EuropeanHirudo "explosion" during the upper Miocene followed by geological events (e.g., Zanclean flood, mountain building) that likely contributed to range restrictions and regional speciation of extant members of the clade.